The Making of Human Dignity in Christian Antiquity - Jadwiga Guerrero van der Meijden (Brill | Schöningh, 2024)
The book examines the late ancient history of one pivotal concept of contemporary culture, that of human dignity, with the view to identifying the moment in history when European culture worked out a systematic category for human axiological status. Whereas some studies concentrate on the notion of dignity in the Renaissance, suggesting that the earlier Christian thought emphasized human insignificance, this analysis reveals that it was the patristic writers who undertook the decisive rethinking of human dignity, primarily in light of the incarnation and the introduction of the feast of Christmas. The volume traces the transformation of the culturally prevalent ancient maxim of self-knowledge (“know thyself”) into an axiological appeal (“know thy dignity”), claiming that it was within that tradition that “dignitas hominis” was popularized and entered the European mindset. In order to demonstrate the lasting changes, the volume outlines patristic axiology's reception in the Middle Ages.